Flipped Classroom Based on Active Learning in Digital Communications Course for Science in Technical Education on New Normal - Thanat Nonthaputha; Montree Kumngern; Sompong Kaewwang; Jirapat Phookwantong; Nawaphol Thepnarin; Kravee Anontree (My University, 2023)
Even the coronavirus disease 2019 (COVID-19) situation has been extricated but it is stilled uncontrollable and spreadable and impacts widely both on economic and academic aspect. The proposed of the study is to investigate and develop the flipped classroom based on active learning for digital communications course students in science in technical education program on new normal. It is designed and focused to prepare when the uncontrollable situation will be occurring. Likewise, this can be taught face-to-face on normal situation. The samples are 70 students who registered in this course and the questionnaire was the research instrument through the simple random sampling technique. The results of this study proved that the students had the highest interested in the active learning through the flipped classroom ($x= 4.89$) and it is flexibility that also can be taught face-to-face and online learning.
Keywords: Innovative Teaching Methods; Education and Work Dynamics